Long Chain Fatty Acids and Virulence Repression in Intestinal Bacterial Pathogens - Mitchell, Mary K.; Ellermann, Melissa (Frontiers in Cellular and Infection Microbiology, 2022)
When bacterial pathogens enter the gut, they encounter a complex milieu of signaling molecules and metabolites produced by host and microbial cells or derived from external sources such as the diet. This metabolomic landscape varies throughout the gut, thus establishing a biogeographical gradient of signals that may be sensed by pathogens and resident bacteria alike. Enteric bacterial pathogens have evolved elaborate mechanisms to appropriately regulate their virulence programs, which involves sensing and responding to many of these gut metabolites to facilitate successful gut colonization. Long chain fatty acids (LCFAs) represent major constituents of the gut metabolome that can impact bacterial functions. LCFAs serve as important nutrient sources for all cellular organisms and can function as signaling molecules that regulate bacterial metabolism, physiology, and behaviors. Moreover, in several enteric pathogens, including Salmonella enterica, Listeria monocytogenes, Vibrio cholerae, and enterohemorrhagic Escherichia coli, LCFA sensing results in the transcriptional repression of virulence through two general mechanisms. First, some LCFAs function as allosteric inhibitors that decrease the DNA binding affinities of transcriptional activators of virulence genes. Second, some LCFAs also modulate the activation of histidine kinase receptors, which alters downstream intracellular signaling networks to repress virulence. This mini-review will summarize recent studies that have investigated the molecular mechanisms by which different LCFA derivatives modulate the virulence of enteric pathogens, while also highlighting important gaps in the field regarding the roles of LCFAs as determinants of infection and disease.